Contribution to the knowledge of biology, natural enemies and damage of Ctenarytaina eucalypti (Homoptera: Psyllidae) - PINZÓN-F., OLGA PATRICIA; GUZMÁN-C., MERCEDES; NAVAS-N., FRITZ (Revista Colombiana de Entomología, 2002)
Introduction of a species of psyllidae attacking young tissues of different Eucalyptus species is known from Australia, where it is native, Europe, North and South America since the 1800 · s. The Psillidae began to be found in second turn plantations of E. globulus Labill surrounding the Sabana of Bogota in 1994. In order to confirm its taxonomical identity as well as to investigate its biology, habits, natural enemies and damage characteristics, observations in the field, greenhouse and semicontroled conditions in the laboratory (15ºC y 80% H.R.) were performed. This species of psyllidae was identified as Ctenarytaina eucalypti Maskell and is believed to be a potential pest in Colombian forests. The occurrence of two to three generations per year was determined, as well as the morphological characteristics, biology, and habits of each one of the development stages that occur in young branches and leaves in nursery and second-growth plantations. Natural control of this species of Psyllidae is achieved by predators of two species of Syrphidae (Díptera) and one of Hemerobiidae (Neuroptera). A preliminary laboratory test suggests that the Syrphidae species is a more efficient predator of the studied species of Psyllidae than is the hemorobiid